Immunological aspects of the lethal HIV / COVID-19 coinfected cohort - A. I. Mazus; E. V. Tsyganova; A. S. Zhilenkova; N. V. Glukhoedova; M. D. Geyne; Yu. A. Anikina; Yu. G. Parkhomenko; N. V. Mozgaleva; P. A. Vedyapin; O. A. Tishkevich (Журнал инфектологии, 2023)
SARS-CoV-2 pandemic is now a global medical and social problem. Little is known about its impact on some vulnerable subgroups, such as immunocompromised patients. Therefore, there is still a strong interest in exploring the impact of SARS-CoV-2 infection among HIV-positive individuals worldwide.   Aim of the study: to analyze immunological aspects of the deceased patients with HIV/COVID-19 coinfection.   Materials and methods. We provided retrospective analysis of 258 patient’s electronic medical records. All patients were admitted to the Infectious diseases hospital № 2 with HIV / COVID-19 coinfection and died in May 2020 – February 2022. Standard immunological parameters were analyzed like CD4+, CD8+ counts and immunoregulatory index for different patient’s subgroups. Statistical data processing was provided by SPSS 17 version (allowable error E = 5 %).   Results and discussion. The study demonstrated CD4+ and CD8+ reduction in HIV-infected with COVID-19. Late HIV-presenters didn’t display such phenomenon probably because of immune system exhaustion. COVID-19 itself in some cases could lead to immunodeficiency worsening due to depletion of T cell populations in HIV-patients on effective antiretroviral therapy.   Conclusion. Comprehension of different immunological characteristics in HIV / COVID-19 coinfected patients could improve therapeutic approaches for this challenging cohort.